The STUDY OF QUARTER-LIFE CRISIS EXPERIENCED BY MARI IN NOVEL AM I THERE YET? BY MARI ANDREW - santoso (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2023)
The purpose of this research and analysis is to find out the phases of the quarter-life crisis faced by the main character, Mari Andrew, and how she conquered them in her novel Am I There Yet? To get the answers related to the quarter-life crisis experienced by Mari Andrew, the writer tries to formulate these problems into two questions, which are: (1). Which phase of quarter-life crisis experienced by the character Mari in the novel? (2). How does Mari conquer the quarter-life crisis in the novel Am I There Yet? In analysing and conducting the research on the quarter-life crisis of the main character in the novel Am I There Yet? the writer uses sociological and psychological approaches. The sociological approach is used to analyze the social phenomenon of the quarter-life crisis experienced by the main character Mari in the novel and the psychological approach is used to analyze the psychology of Mari as she conquers the quarter-life crisis period. The writer also conducts library research in completing this study. Several theories regarding the phases of the quarter-life crisis and the ways to conquer the quarter-life crisis are used by the writer as references and supporting material to support the research and analysis that is conducted by the writer. The writer applies the theory of phases of the quarter-life crisis that is developed by Robinson, Wright, and Smith to analyze Mari Andrew’s phases of the quarter-life crisis. The benefit of this research is to understand how people in their twenty’s express developmental crises. And the writer also applies the theory of conquering the quarter-life crisis that is developed by Mary Traina to analyze Mari Andrew’s ways to conquer the quarter-life crisis. By analyzing this, the writer expects the results of the research will not only applicable for literature character but also a real human. At the end, the writer discovers that Mari Andrew had a crisis when she was in her 20s. From that crisis, she was able to go through in several phases and came to a phase where she could better understand herself and what she wanted. And she began to make peace with herself. Because she experienced a quarter-life crisis, she was also able to find ways to conquer the crisis in several ways and lead her to a life that was more focused and more self-aware